Morphological, morphometrical and ultrastructural characterization of Phrynops geoffroanus' (Testudines: Chelidae) blood cells, in different environments - Saranz Zago, Carlos Eduardo [UNESP]; da Silva, Tiago Lucena [UNESP]; Afonso da Silva, Maria Isabel [UNESP]; Rodrigues Venancio, Larissa Paola [UNESP]; Mendonca, Priscila Pasqueetto [UNESP]; Falleiros Junior, Luiz Roberto [UNESP]; Vizotto, Luiz Dino [UNESP]; Taboga, Sebastiao Roberto [UNESP]; Bonini-Domingos, Claudia Regina [UNESP]; Vilela de Azeredo-Oliveira, Maria Tercilia [UNESP]; de Oliveira, Classius [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
The aim of this study was to evaluate the formed elements in the periferical blood of two amostral groups of Phrynops geoffroanus: one from an urban environment under domestic sewage dumping, and another from a non-contaminated environment. Blood samples of 36 animals (females and males) were collected through cardiocentesis. Sixteen specimens were from the urban environment, and 20 were from a control environment. Samples of blood tissue were used for light microscopy analysis, and also for morphometric analysis of red blood cells. For the ultrastructural analysis, blood samples of 2 animals were used. The formed elements found, using morphological and ultrastructural analysis were: nucleated red blood cells; thrombocytes; neutrophils, lymphocytes, monocytes, basophils; eosinophils; heterophils, and azurophils. The morphometric analysis of all red blood cells parameters examinated in females showed a statistically significant difference, but in males just the nuclear area showed difference between the specimens of the two environments. The elements identified by light microscopy were elucidated by electron transmission microscopy. This P. geoffroanus study is the first one that makes a correlation between these environments and the description of turtle's blood cells, thus contributing to the identification of the hematological characteristics of this group. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Phrynops geoffroanus; Turtles; Blood cells; Morphology; Ultrastructure